Middle Meningeal Artery Embolization for Primary Treatment of a Chronic Subdural Hematoma in a Pediatric Patient: A Systematic Review of the Literature and Case Report. Issue 1 (3rd January 2023) - Paro, Mitch R.; Ollenschleger, Martin D.; Fayad, Mohamad F.; Bulsara, Ketan R.; Stoltz, Petronella; Martin, Jonathan E.; Bookland, Markus J.; Hersh, David S.
Abstract : BACKGROUND: Middle meningeal artery (MMA) embolization is becoming increasingly studied as a safe, effective treatment for chronic subdural hematoma (cSDH) in adults. Among pediatric patients, however, MMA embolization for cSDH has been rarely described, and the potential benefit of this approach for pediatric patients remains unknown. OBJECTIVE: To systematically review the literature and identify cases of pediatric MMA embolization for cSDH. We also report our experience with pediatric MMA embolization. METHODS: A systematic review of the literature was performed to identify cases of pediatric MMA embolization for cSDH. Inclusion criteria included English language availability and pediatric age defined as less than 18 years. A pediatric patient treated with MMA embolization was also identified at our institution. RESULTS: Five cases of pediatric MMA embolization for cSDH were identified in the literature. Two were associated with arachnoid cysts, 2 with antiplatelet/anticoagulation therapy, and 1 with abusive head trauma. There were no adverse events, and all patients demonstrated clinical and radiological improvement on follow-up. At our institution, a previously healthy 8-year-old male was found to have a right-sided acute-on-chronic SDH during a headache evaluation. A diagnostic angiogram was performed to rule out a dural arteriovenous fistula, and right-sided MMA embolization was performed concurrently. Rapid clinical and radiological improvement was observed, with complete resolution by 6 months. CONCLUSION: MMA embolization may represent a treatment option for pediatric patients with cSDH. Abstract :